Growing of ZnWO₄ single crystals from melt by the low thermal gradient Czochralski technique - Galashov, E.N.; Gusev, V.A.; Shlegel, V.N.; Vasiliev, Ya.V. (Functional Materials, 2009)
The shape formation regularities of ZnWO₄ scintillation crystals grown along the [001] and [010] directions by the low-temperature-gradient Czochralski technique have been studied. It has been established that increasing crystallization speed is accompanied by the development of faceted shapes at the crystallization front. The inclusion-free crystals can be grown with both completely rounded or completely faceted solid-liquid interface, while the coexistence of faceted and rounded surfaces may result in capturing inclusions at their boundaries. The inclusion-free ZnWO₄ crystals of 45 mm diameter and the length up to 150 mm have been grown. Absorption spectra of the crystals prior to and after annealing have been measured. For the samples of d40 and l=40 mm size, the energy resolution of 11 % for gamma radiation with the energy of 662 keV has been obtained.